Exploring the Potential for Social Conflict in Rusunawa Development : For Sustainable Urban Planning in Bandung - Aris Toening Winarni; Permadi Mulajaya (International Journal of Social Science and Humanity, 2025)
This research aims to analyze the potential for social conflict in the development of Rusunawa Sadangserang in Bandung City through a sustainable planning perspective. This study employs a case study approach, utilizing in-depth interviews and source triangulation for data collection and analysis. The findings suggest that the potential for conflict arises from three primary sources, namely changes in land use, inequality in the provision of residential units, and unclear land ownership status. Changes in the function of Sadangserang Market and Sadangserang Terminal risk triggering resistance from traders and drivers. The imbalance of commercial units and subsidies can create access conflicts for low-income groups. Uncertain land ownership status is also prone to disputes. Therefore, a sustainable planning strategy is needed that involves public participation, socio-economic surveys, and clarification of land status. In this way, it is hoped that Rusunawa Sadangserang can make an optimal contribution to providing harmonious and fair housing in the city of Bandung.